Gender and scientific publishing: structural inequalities and female underrepresentation in leadership positions (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study investigates gender distribution in editorial teams of scientific journals affiliated with the Alagoas Scientific Journals in Focus project, analyzing female representation in leadership positions. Through document analysis, data were collected on the editorial composition of 11 journals, classifying members by gender and function. Results show that while women comprise 40.2% of editorial teams, their representation in strategic positions (e.g., editor-in-chief) is significantly lower (28.5%), with variations across knowledge areas. The research suggests the potential persistence of unequal gender patterns in editorial structures, highlighting the need to discuss institutional policies promoting greater equity.
Keywords: gender equity; scientific journals; inequalities in science